Prevalence and determinants of adolescent childbearing: comparative analysis of 2017–18 and 2014 Bangladesh Demographic Health Survey - Alam, Nazmul; Mollah, Mohammad Manir Hossain; Naomi, Sharin Shahjahan (Frontiers in Public Health, 2023)
Objectives: Bangladesh has one of the highest adolescent fertility rates in South Asia, which prevent women from realizing their full potential in life. This study aimed to compare the prevalence and determinants of adolescent fertility in Bangladesh using data from the 2014 and 2017-18 Bangladesh Demographic and Health Survey (BDHS). Methods: Nationally representative surveys of respondents were selected using a two-stage sampling process. The study recruited 2,023 and 1,951 ever-married women aged 15-19 from 2014 and 2017-18 BDHS surveys, respectively, from rural and urban settings from all eight geographic divisions of Bangladesh. Univariate and multivariate logistic regression models were fit to determine the factors associated with adolescent fertility. Result: The adolescent fertility prevalence rate was 30.8% in 2014 BDHS and 27.6% in 2017-18 BDHS. Marriage at age 13 years or less also reduced significantly in 2017-18 compared to 2014 (12.7% vs 17.4%, respectively). Significantly higher odds of adolescent fertility were found in 2014 among women in the Sylhet Division (adjusted odds ratio (AOR) = 3.0; 95% confidence interval (CI): 1.6 – 6.1) and the Chittagong Division (AOR = 1.8; 95% CI: 1.8-2.7) compared to the Barisal Region; however, in 2017, there were no significant differences was found across the geographic Divisions. Compared to women in the lowest wealth quintile, women in all other quintiles had lower odds of adolescent fertility, with the lowest odds found among women in the wealthiest quintile (AOR=0.3; 95% CI: 0.2-0.6). Women who married at age 14-17 had 60% lower odds of adolescent fertility compared to the women who married at age 10-13. Conclusion: Nearly one-third of married adolescents in Bangladesh were pregnant or had at least one child before their twentieth birthday in 2014, and this was reduced only marginally in 2017-18. Marriage at an early age and income inequalities among families were significant predictors of adolescent fertility in Bangladesh. Policies and interventions should be streamlined to prevent child marriage and income inequalities to address adolescent fertility in Bangladesh.